Expert's opinions on software project effective risk management - Janjua, U.I. (Institute of Electrical and Electronics Engineers Inc., 2016)
To increase the success rate of software project development, the review of literature suggests the need of effective risk management practices. However, significance and varying views regarding software project effective risk management in literature would suggest that the time is ripe for an exploration of the phenomenon; software project effective risk management. In this paper researchers contacted 14 experts of 6 different countries through an open ended questionnaire to take their opinion about software project effective risk management. Results indicated that the most of the experts have consensus about the strategies need to be followed and hurdles need to be removed for effective risk management. Moreover, results indicated that to measure the effectiveness of risk management, it must be viewed in broader context of project success. Â© 2016 IEEE.